The Neural Bases of Emotion Regulation: Reappraisal and Suppression of Negative Emotion - Goldin, Philippe R (2007)
BACKGROUND: Emotion regulation strategies are thought to differ in when and how they influence the emotion-generative process. However, no study to date has directly probed the neural bases of two contrasting (e.g., cognitive versus behavioral) emotion regulation strategies. This study used functional magnetic resonance imaging (fMRI) to examine cognitive reappraisal (a cognitive strategy thought to have its impact early in the emotion-generative process) and expressive-suppression (a behavioral strategy thought to have its impact later in the emotion-generative process). METHODS: Seventeen women viewed 15s neutral and negative-emotion eliciting films under four conditions - watch neutral, watch negative, reappraise negative, and suppress negative - while providing emotion experience ratings and having their facial expressions videotaped. RESULTS: Reappraisal resulted in early (0−4.5s) prefrontal cortical (PFC) responses, decreased negative emotion experience, and decreased amygdala and insular responses. Suppression produced late (10.5−15s) PFC responses, decreased negative emotion behavior and experience, but increased amygdala and insula responses. CONCLUSIONS: These findings demonstrate the differential efficacy of reappraisal and suppression on emotional experience, facial behavior, and neural response, and highlight intriguing differences in the temporal dynamics of these two emotion regulation strategies.